Kajian Jagung dan Mocaf sebagai Bahan Baku Beras Artifisial Menggunakan Alat Ekstruder Ulir Tunggal - Yossi Wibisono; Heri Warsito (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2024)
People's dependence on rice is currently very high and this need must be met by imports, so that the need for imports is certain to increase from time to time, both in terms of quantity and purchase price. Indonesia is currently ranked 63rd out of 113 countries in terms of food security, The Increasing consumption of rice is also one of the causes of the increase in the number of diabetes sufferers, considering that rice is a product with a high GI value. One solution that can be done is to replace rice with artificial rice made from cheap local ingredients with a low GI value. One of them is corn which is a leading local commodity. Politeknik Negeri Jember has conducted research on the ideal formulation of artificial rice, namely using 50% corn and 50% mocaf and has optimized the artificial rice making tool, namely a single screw extruder. The aim of this research is to produce a method for making artificial rice with low GI, economical and affordable using local corn and mocaf fermented with L. plantarum 15420 bacteria and produced using a single screw extruder and studying the chemical and physical aspects of artificial rice. The resulting artificial rice has an ash content of 0.52%, , amylose conten of 13.11%, amylopectin conten of 30.28% (with a ratio of 31:68), protein conten of11.2%, Ca conten of 0.04%, fat conten 0.5%, water conten of 11.3% and resistant starch conten of 6.4%. The GI value of artificial rice is 51.2. Regarding the feasibility study, the R/C ratio value was 1.31. The price of the artificial rice Polije produces is affordable for the entire community at Rp. 37,500,- per package (2.5 kg) which is more economical compared to IR64 rice.